MANAJEMEN KECEMASAN MASYARAKAT DALAM MENGHADAPI PANDEMI COVID-19 - Andini Permana Kartika Putri; Ardi Septiawan (Academica: Journal of Multidisciplinary Studies, 2020)
In the difficult conditions of the Covid-19 pandemic, people tend to experience anxiety. Anxiety is worrying about things out of control in the future. In anxiety management, there are three kinds of techniques, namely emotional regulation, cognitive behavioral techniques, and relaxation. Emotional regulation is a technique for balancing emotional states by changing the way emotions are expressed. CBT is a technique in which an individual's behavior and emotions can be controlled through a process of learning (cognition) and habituation (behavior). Finally, relaxation is a condition of resting the body by stretching, breathing, and taking a comfortable position so that the mind becomes calm and stable so that individuals can respond to these difficult conditions wisely. In this study, anxiety management is explored using a qualitative approach with literature study techniques.Keywords:Â Anxiety; Anxiety management; Cognitive Behavioral Thechniques; Emotion Regulation; Relaxation.